Psychosocial benefits of dental corrections in adolescents and adults - Alhammad, Khalid S.; Alfaqeeh, Maali E.; Hissah M. Alhazmi; Alqahtani, Ali S. (International Journal Of Community Medicine And Public Health, 2024)
Dental corrections play a pivotal role in enhancing psychosocial health among adolescents and adults, offering significant improvements in self-esteem, social interactions, and overall psychological well-being. Adolescents, who are particularly vulnerable to social pressures and self-esteem issues, benefit greatly from orthodontic treatments that address malocclusions and misalignments. These treatments lead to heightened self-confidence, reduced social anxiety, and fewer instances of bullying, fostering healthier social development and mental health. In adults, dental corrections not only improve aesthetics but also enhance professional and personal interactions. Improved dental health leads to increased social engagement, better communication, and higher levels of life satisfaction, reducing social withdrawal and depressive symptoms. The ability to smile confidently, speak clearly, and eat comfortably without feeling self-conscious is crucial for mental well-being. Individuals with enhanced dental aesthetics report significant improvements in their quality of life, engaging more in social activities and forming meaningful relationships. Research supports the profound impact of dental corrections on reducing anxiety, depression, and social isolation. Adolescents and adults who undergo these treatments experience a notable boost in self-esteem and confidence, which translates into improved academic performance, career opportunities, and overall life satisfaction. The broader implications of these findings emphasize the need for dental care practices to incorporate psychosocial considerations, enhancing the overall patient experience and promoting long-term mental health benefits. By prioritizing the psychosocial outcomes of dental treatments, dental professionals can significantly improve the quality of life for their patients, contributing to their overall well-being and societal participation.